Pengaruh Konseling Individual Teknik REBT Terhadap Kemampuan Memecahkan Masalah pada Siswa Korban Bullying di Kelas VIII Mesra Pematangsiantar - Nasution, Nani Barorah; Azzahra, Luthfi (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to use the Rational Emotive Behavior Therapy (REBT) technique with the aim that it can help students to be able to live more productively by thinking rationally. The research approach used is a quantitative approach with the type of quasi-experimental research (Quasi Experiment) using a design one group pretest and posttest. The type of research used is descriptive research. The sampling technique in this study was purposive sampling technique. The data collection instrument used in the research is using a psychological scale about problem solving skills. By using questioner and interviews to collect data in this study. Based on the results of the Wilcoxon test, the results of changes in the ability to solve problems of students who were victims of bullying can be proven from the results of data analysis, namely the value of J_count = 16.4, α = 0.05, and N = 5 obtained J_table = 0 . So, J_count>J_table where 16.4 > 0, which means the hypothesis can be accepted. With the influence of individual counseling services, rational emotive behavior therapy (REBT) techniques can help students solve problems and increase the level of ability to solve problems for victims of bullying. Through this research, it is hoped that it can teach students how to solve the problem of victims of bullying supported by positive thoughts and attitudes.